Environmental Knowledge, Attitudes and Behavior of English as Foreign Language Students: A Case Study In FLSH, Meknes, Morocco - Laabidi, Hicham; Charafi, Maryam (Journal on Studies in English Language Teaching (JOSELT), 2023)
Morocco's environmental issues are worsening; making it critical to gauge the environmental knowledge, attitudes, and actions of the demographic deemed to carry on their treatment as a means to enhance the conduct of future generations towards the environment. Despite the rising corpus of research in this area, very limited studies addressed students’ environmental awareness, and some overlooked accounting for university students. This study intended to examine students' environmental awareness and how it influences their pro-environmental behavior. The study included 100 students from the School of Arts and Humanities, Meknes. Questionnaires were distributed online to collect data, which subsequently was analyzed using descriptive statistics. According to the study's findings, students' environmental awareness is positive and encouraging. The findings also revealed that a significant proportion of students were uninformed about environmental facts and did not engage in any environmental practices at all; indicating the need for a practical strategy to re-examine and reorient the approach of EE in the Moroccan context in order to ensure that it not only raises learners' environmental awareness but also fosters a sense of responsibility, which is critical in ensuring environmental sustainability.